Developmentof a bar of cereals, nuts and tropical fruits enriched with hydrolyzed collagen (@limentech, Ciencia y Tecnología Alimentaria, 2023)
Cereal bars are a healthy food due to their nutrient content resulting from the combination of cereals with other ingredients such as fruits. However, the syrups used as binders in the product imply an increase in sugar content. The use of hydrolyzed collagen as a replacement for sugar syrups can be an alternative in the production of cereal bars with lower sugar content. The objective of this study was to create a cereal, nut, and tropical fruit bar enriched with hydrolyzed collagen. Three formulations of the bar were processed, varying the concentration of hydrolyzed collagen against a control without collagen addition. A sensory analysis was conducted to determine the most accepted formulation, which was then analyzed for its physicochemical and microbiological characteristics. The results showed that the cereal bar with 20% hydrolyzed collagen had the highest acceptance, provided 9.22% protein, 67.25% carbohydrates, 18.9% iron, and 9.96% zinc, and had good microbiological quality. The use of hydrolyzed collagen as a binding agent in the formulation of cereal bars is recommended.
Keywords: Cereal bars; hydrolyzed collagen; nuts; glutinating agents